Coffee table with sliding book case / Che Mohamad Azrul Che Lah and Norashikin Kamarudin - Che Lah, Che Mohamad Azrul; Kamarudin, Norashikin (2015)
This research was conducted to assess feedback from users about the importance of multifunctional furniture. The design as the product is the major for this study. After the coffee table has produced the survey forms were distributed to 96 respondents randomly. Then, the SPSS was applied to analyze the data obtained. Most of the respondents give positive feedback to the product design on material used, suitability of the product design, friendly user and will function. Overall, the coffee table is well accepted as multifunction furniture.